Tecnologia e mudança no currículo de uma escola técnica - Esteves, Marta Maria (2010)
The evolution of technology is present in many aspects of everyday life for most people in the simplest tasks like going to the bank to receive their salaries, shop, communicate, among other things. All this development is being perceived in everyday schools and find out what are the reasons influencing the change of the curriculum of technical courses at a school founded in the fifties and how technology is in it is the objective of this project which raises the initial hypotheses of determinants that bring about this change as performance of the faculty members, composed of a majority of teachers working in the labor market, the vocation of the school or the requirement of the labor market. This research will also address the challenges of the school to adapt to the world of technology and especially the importance of the teacher to support that change as the protagonist, along with their students. As this is a technical school, there is the close and necessary relationship with the labor market, with a reference to employability and technology education, which requires a pre-defined curriculum to meet the labor market, but that changes frequently because of its educational nature. To arrive at conclusions, we analyzed official documents governing the national vocational education, school documents, meetings, focus groups and questionnaires with students and interviews with teachers and coordinators. There has been a dialogue between "speeches" and were created units of meaning of the questions most relevant to the changes in the curriculum and the integration of technology. It was concluded that the agents that cause the changes in the curriculum and promote the insertion of the technology are: faculty members, formed mostly by professional teachers, the labor market and working students, and the methodology used by the school, especially by the time it is "left over" in the classroom